Donor chimerism and immune reconstitution following haploidentical transplantation in sickle cell disease - Chu, Yaya; Talano, Julie-An; Baxter-Lowe, Lee Ann; Verbsky, James W.; Morris, Erin; Mahanti, Harshini; Ayello, Janet; Keever-Taylor, Carolyn; Johnson, Bryon; Weinberg, Rona S.; Shi, Qiuhu; Moore, Theodore B.; et al. (Frontiers in Immunology, 2022)
Abstract Background: We previously reported the initial results of a phase II multicenter transplant trial using haploidentical parental donors for children and adolescents with high-risk sickle cell disease achieving excellent survival with exceptionally low rates of graft-versus-host disease and resolution of sickle cell disease symptoms. Objectives: To investigate human leukocyte antigen (HLA) sensitization, graft characteristics, donor chimerism, and immune reconstitution in these recipients. Methods: CD34 cells were enriched using the CliniMACS® system with a target dose of 10 x 106 CD34+ cells/kg with a PBMNC addback dose of 2x10^5 CD3/kg in the final product. Pre-transplant HLA antibodies were characterized. Donor chimerism was monitored 1-24 months post-transplant. Comprehensive assessment of immune reconstitution included lymphocyte subsets, plasma cytokines, complement levels, anti-viral T-cell responses, activation markers, and cytokine production. Infections were monitored. Results: HLA antibodies were detected in 7 of 11 (64%) evaluable patients but rarely reacted to donor antigens. Myeloid engraftment was rapid (100%) at a median of 9 days. At 30 days, donor chimerism was 93-99% and natural killer cell levels were restored. By 60 days, CD19 B cells were normal. CD8 and CD4 T-cells levels were normal by 279 and 365 days, respectively. Activated CD4 and CD8 T-cells were elevated 100-365 days post-transplant while naïve cells remained below baseline. Tregs were elevated 100-270 days post-transplant, returning to baseline levels at one year. At one year, C3 and C4 levels were above baseline and CH50 levels were near baseline. At one year, cytokine levels were not significantly different from baseline. Conclusions: These results suggest that haploidentical transplantation with CD34-enriched cells and peripheral blood mononuclear cell addback results in rapid engraftment, sustained donor chimerism and broad-based immune reconstitution.